Implikasi Penerapan Hukum Pidana Adat dalam Pasal 2 KUHP terhadap Asas Legalitas dalam Sistem Hukum Pidana Indonesia - Yanuardi Yogaswara; Tata Surwita; Dewi Asri Yustia (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research discusses customary criminal law in Article 2 of Indonesia's new Criminal Code (KUHP), which reflects the country's social and cultural diversity. Customary criminal law, with its unique characteristics rooted in the values and social norms of indigenous communities, offers a different approach to conflict resolution compared to formal criminal law. It enriches the criminal justice system with aspects of restorative justice and creates space for the recognition of living law within society. However, this integration poses challenges, particularly regarding legal certainty and the principle of legality, considering that customary criminal law is often unwritten and variable. The method used is normative, involving legal research conducted through the study of literature or secondary data. The research is descriptive-analytical, focusing on the existence of customary law within national criminal law. Using a qualitative juridical approach, the analysis is based on legal principles and norms, studying legislation, literature, and scholarly writings. This study shows that the recognition of customary criminal law in Article 2 of the new Criminal Code presents challenges and opportunities for Indonesia's criminal justice system. This integration supports restorative justice and reflects the country's cultural diversity, but it also requires careful handling of legal certainty and the principle of legality. The need for clear conflict resolution mechanisms and additional regulations is crucial to maintaining a balance between customary legal traditions and the requirements of modern criminal law.